Uresničevanje ciljev Nacionalnega gozdnega programa po meri lastnika? - Andoljšek, Andrej (Gozdarski vestnik, 2009)
The article deals with the National Forest Program from the view-point of the forest owner. It presents the dilemmas arising from the owners' and public interests from the environmental, economic and social aspect.
Keywords: gozdno gospodarstvo; nacionalni programi; gozdovi; lastništvo